Impact of Zumba on Cognition and Quality of Life is Independent of APOE4 Carrier Status in Cognitively Unimpaired Older Women: A 6-Month Randomized Controlled Pilot Study. (20th January 2020) - Stonnington, Cynthia M.; Krell-Roesch, Janina; Locke, Dona E. C.; Hentz, Joseph G.; Dueck, Amylou C.; Geda, Yonas E.; Tariot, Pierre N.; Caselli, Richard J.
Objective: To investigate the association of a 6-month Zumba intervention with cognition and quality of life among older cognitively unimpaired apolipoprotein ∊4 (APOE4) carrier and noncarrier women. Methods: Fifty-three women were randomly assigned to either twice-weekly Zumba group classes or maintenance of habitual exercise (control group) for 6 months. At baseline, 3, and 6 months, all participants underwent neuropsychological, physical activity, and quality-of-life assessments. Results: Overall, neuropsychological test scores and level of physical activity did not differ between intervention and control groups at any time. However, compared to the control group, quality of life was higher at 3 months, and visuospatial working memory and response inhibition improved more in the intervention group by 6 months. Apolipoprotein ∊4 status did not affect the results. Discussion: Zumba may strengthen performance on visuospatial working memory among cognitively unimpaired older women but this needs to be tested in a larger clinical trial.